Bacterial Power: An Alternative Energy Source - Fonseca, Bruno M. (2022)
The demand for energy and the limited supply of fossil fuels and their impact in the environment have required the development of alternative energy sources. Among the next generation of energy sources, microbial fuel cells (MFCs) have emerged as a promising technology due to their ability to recover energy from wastewaters in the form of electricity using electroactive microorganisms as catalysts. Among the various factors that affect power generation performance in MFCs, the efficiency of extracellular electron transfer (EET) is one of the most important. Several enzymes, specifically multiheme cytochromes, have been implicated in this process although the electron transfer chain organization remains to be fully understood. In this chapter, we review in detail the mechanisms that support EET from electroactive microorganisms to the anode in MFCs. We focus on the model organism Shewanella oneidensis MR-1, due to the existence of an extensive molecular characterization of its EET processes. The recent developments in the characterization of the multiheme cytochromes involved in these mechanisms will also be reviewed.